KODE ETIK APARATUR SIPIL NEGARA - Juanda Nawawi (FISIP UNHAS, 2019)
Abstract This paper aims to describe the results of community service collaboration with reseacrh institutions and comunity service and staffing agencies and the development of the human resources of the Wajo district goverment regarding the code of ethics of the state civil apparaturs. The code of ethics of the state civil apparaturs is a guideline of attitudes, behavior and deeds in carrying out their duties and in their daily life. The code of ethics can be seen from several dimensions namely professionalism ethics, enforcement of the code of ethics, violation of the code of ethics, and sanctions violating the code of ethics. Keywords: Code of ethics, state civil apparaturs, community service collaboration Abstrak Tulisan ini bertujuan untuk menggambarkan hasil pengabdian masyarakat kerjasama lembaga penelitian dan pengabdian masyarakat dan badan kepegawaian dan pengembangan sumber daya manusia Pemerintah Daerah Kabupaten Wajo tentang kode etik Aparatur Sipil Negara. Kode etik Aparatur Sipil Negara adalah pedoman sikap, tingkah laku, dan perbuatan didalam melaksanakan tugasnya serta dalam pergaulan hidup sehari-hari. Kode etik dapat dilihat dari beberapa dimensi yaitu etika profesionalisme, penegakan kode etik, pelanggaran kode etik, dan sanksi pelanggaran kode etik. Keywords: Kode etik, aparatur sipil negara, pengabdian masyarakat